Technological ecologies and sustainability / - Heidi A. McKee,DeVoss, Dànielle Nicole,Selfe, Richard,McKee, Heidi A,DeVoss, Dáanielle Nicole. (Utah State University Press, 2009)
Together, computerized writing environments (e.g., physical spaces, hardware, software, and networks) and the humans who use and support such technologies comprise complex ecologies of interaction. As with any ecology, a human-computer techno-ecological system needs to be planned, fostered, designed, sustained, and assessed to create a vibrant culture of support at the individual, programmatic, institutional, and even national and international level. Local and larger infrastructures of composing are critical to digital writing practices and processes. In academia, specifically, all writing is increasingly computer-mediated; all writing is digital. Unfortunately, at far too many institutions, it is difficult to sustain ecologies of digital writing. How then to best plan, foster, design, sustain, and assess the complex ecologies framing the study and practice of digital writing that we do (or hope to do) as teachers, scholars, learners, and writers? The audience for this collection is teachers, scholars, administrators, and graduate students working in fields of composition studies, computers and writing, technical/professional communication, literature, education, and English education. We all face the same dilemma: More and more of our work and instruction takes place in electronic environments, but budget constraints and assessment mandates loom, and often our positions within or institutions prohibit us from active participation in central computing endeavours. This necessarily multivocal collection refines our discussions of the many components of sustainability, providing contextual, situated, and flexible modes and methods for theorizing, building, assessing, and sustaining digital writing ecologies.
Bibliographic Level Mode of Issuance: Monograph
Keywords: English language – Rhetoric – Computer-assisted instruction. English language – Rhetoric – Study and teaching. Report writing – Study and teaching. Electronic portfolios in education. Hypertext systems.; English language; Report writing; Electronic portfolios in education; Hypertext systems; English; Languages & Literatures; English Language